Influence of Father Support for Early Breastfeeding Initiation among Cesarean Mothers in Lower-Middle-Income Countries: A Literature Review - I Gede Shivananda Vidyana Puja; Made Kurnia Widiastuti Giri; Ketut Indra (Cerdika: Jurnal Ilmiah Indonesia, 2026)
The role of managerial economics in decision-making, company performance, and organizational governance is discussed in this study. The review results indicate that managerial economics serves as a conceptual framework and practical tool for managers to integrate microeconomic and macroeconomic theories as well as quantitative approaches to make better business decisions. Budgeting methods, cost-benefit analysis, and management accounting systems have proven effective in enhancing managers' ability to assess performance through planning, controlling, and evaluation. Human resource factors—such as managerial leadership and employee motivation—also play an important role in improving organizational productivity. Additionally, research shows how a company's ownership structure, dividend policy, and management systems impact investor value and trust. Conversely, digital transformation, board diversity, and the Islamic economy represent external and normative factors that influence business sustainability in today's highly dynamic world. Overall, the results of this review indicate that managerial economics is useful both as a theory and a practical practice to support corporate competitiveness, innovation, and sustainability. To face the uncertainty of the global business environment, companies and community groups must adopt a flexible, data-driven, and ethically oriented approach to managerial economics.